Refining processes handbook. - Parkash, Surinder, ....- (Amsterdam : Elsevier, 2003)
Samenvatting:Besides covering topics like catalytic cracking, hydrocracking, andalkylation, this volume has chapters on waste water treatment and theeconomics of managing or commissioning the design of a petroleumrefinery. Found only in this volume is material on operating a jointlyowned and operated refinery. (Over the last decade, the ownership of manyrefineries has shifted to small companies, from the large, integratedcompanies. Because of this shift, many refineries are now jointly ownedand operated.) Filled with handy process flow diagrams, this volume isthe only reference that a chemical engineer or process manager in apetroleum refinery needs for answers to everyday process and operationsquestions.
Keywords: Aardolieindustrie; Aardolieraffinage